Testing Guidano's model of psychopathology in eating-disordered individuals : a multiple case study - Hajayiannis, Helen (Rhodes University, Faculty of Humanities, Department of Psychology, 1998)
This thesis sets out to critically examine Guidano's model of psychopathology in eating-disordered individuals . The literature review highlights the diverse etiological approaches that have been taken in understanding eating disorders. Guidano's model is presented as an alternative to traditional approaches . It is a developmental, unitary model of psychopathology, conceptualised within a systems/process-oriented approach to organised complexity. Within a qualitative framework, case study methodology is utilised to test the viability and limitations of Guidano's model. Four in-depth case histories are presented which offer appropriate material for the testing of the model. The data is analysed using the reading guide method and presented in terms of the four features of Guidano's model: (1) dysfunctional patterns of attachment; (2) sense of self; (3) major themes on systemic coherence; (4) common coping strategies. The findings of the research support Guidano's model of psychopathology in eating-disordered individuals. The findings are: (1) attachment styles are ambiguous, "intrusive, and enmeshed; participants experience a disappointment in the preferential attachment relationship; (2) that participants' sense of self is blurred and wavering; (3) the major theme on systemic coherence is the oscillation between seeking and avoiding intimacy; (4) common coping strategies are: the seeking of supportive intimacy with minimal self-exposure; withdrawal into the self; perfectionism; the development of an eating disorder; continuous thoughts about food, eating, and weight which prevents participants from becoming aware of the real issues confronting them. An evaluation of Guidano's model in terms of its specific contribution to knowledge and research on the role of father in child and adolescent psychopathology, as well as how father effects evidence in eating disorders, demonstrates the model's value as an explanatory tool and raises implications for future treatment, theory, and research practices of eating-disordered individuals.
Keywords: Psychology, Pathological; Eating disorders -- Case studies; Guidano, V F; Eating disorders -- Etiology